2022
DOI: 10.1111/jam.15614
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm activities of novel antimicrobial peptide DP7 against the periodontal pathogen Porphyromonas gingivalis

Abstract: Aims: Accumulating evidence suggests that Porphyromonas gingivalis is closely associated with the development of various chronic inflammatory diseases, particularly periodontitis. This study investigated the antibacterial activity and action mechanism of a novel antimicrobial peptide (AMP), DP7, against P. gingivalis. Methods and Results:The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for DP7 were determined via a broth microdilution method, revealing an MIC of 8 μg ml −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Peptide variants of BmKn-2 from scorpion venom exhibited anti-biofilm activity against Salmonella isolates [94]. With respect to oral health, Jiang et al showed that AMP DP7 inhibited planktonic and biofilm forms of Porphyromonas gingivalis [95]. MPX, an AMP from wasp venom, was shown to be effective against Actinobacillus pleuropneumonia, a highly contagious pathogen causing significant economic loss to the pig industry [96].…”
Section: Fungimentioning
confidence: 99%
“…Peptide variants of BmKn-2 from scorpion venom exhibited anti-biofilm activity against Salmonella isolates [94]. With respect to oral health, Jiang et al showed that AMP DP7 inhibited planktonic and biofilm forms of Porphyromonas gingivalis [95]. MPX, an AMP from wasp venom, was shown to be effective against Actinobacillus pleuropneumonia, a highly contagious pathogen causing significant economic loss to the pig industry [96].…”
Section: Fungimentioning
confidence: 99%
“…Numerous natural peptides exhibit a wide range of antimicrobial activities, including antibacterial, antiviral, and antifungal effects 229 . These peptides exert their actions through various mechanisms, such as disruption of bacterial cell membranes, 230,231 membranelysis, 232 and modulation of host immune responses 233 . Through structural optimization and synthesis of these natural peptides, synthetic peptides with enhanced antimicrobial activity can be obtained 234,235 .…”
Section: Biomedical Applications Of Peptides and Pasmentioning
confidence: 99%